A Review of Teachers' Sentiments and Attitudes in Inclusive Education in China - Yang, Min; Yu, Chao (Frontiers in Psychology, 2021)
Students should receive appropriate and comprehensive educational opportunities regardless of their ethnicity, gender, and even probable disabilities or exceptionalities. For this purpose, governments and educational boards have agreed to investigate the concept of inclusive education as a new paradigm where students can benefit from materials and classroom environment whether they are ordinary students or students with special needs. Chinese educational government has also adopted inclusive education within its pedagogic program since the middle of the 1990s. In this regard, some well-known researchers highlighted the impact of teachers’ attitudes, sentiments, and concerns in inclusive education as a driving force toward student support and rapport. Moreover, the cultural background has also been emphasized in studies of inclusive education. Hence, it is necessary to employ the proposed and standardized attitude, sentiment, and concern scales, as well as the translated version to measure the factors affecting the proper implementation of inclusive pedagogy. The present study was an attempt to review related studies on teachers’ attitudes and sentiments, particularly in China. Findings suggest that cultural differences might not necessarily contribute to the successful implementation of inclusive programs; however, pre-service or in-service teachers have demonstrated that higher levels of sentiment (efficacy), as well as positive attitude, can lead to the efficient provision of materials and building a supportive classroom environment for ordinary students and more importantly student with special needs.